Sex-specific metabolic effects of Treg expansion in db/db mice - Pérez-Martínez, Daniel; Canz, María Jose; Torras-Peyrotón, Elisabet; Alvarez-Guaita, Anna; Ramos-Pérez, Lorena; Hernández, Cristina; Simó, Rafael; Llorián-Salvador, María (Frontiers in Immunology, 2025)
IntroductionType 2 diabetes mellitus (T2D) is characterized by chronic, low-grade inflammation and immune dysregulation, contributing to insulin resistance and metabolic complications. Regulatory T cells (Tregs) are key modulators of immune homeostasis, and their therapeutic expansion has shown promise in limiting inflammation. Here, we investigated whether in vivo Treg expansion could modulate metabolic and inflammatory responses in T2D in a sex-specific manner.MethodsMale and female db/db and db/+ mice received intraperitoneal injections of IL-2/anti-IL-2 (JES6-1) complexes for six weeks to induce endogenous Treg expansion. Body weight, blood glucose, and insulin levels were monitored to calculate HOMA-IR. Plasma inflammatory and anti-inflammatory mediators (CRP, adiponectin, IL-10, IL-13, CCL3) were quantified by bead-based immunoassays. Hepatic triglycerides and gene expression of Foxp3, F4/80, Pparγ, Il10 and Il13 were analyzed by biochemical assays, western blot, and RT-qPCR.ResultsTreg expansion reduced weight gain in db/db mice independently of food intake. Female mice displayed lower HOMA-IR, decreased CRP, and increased adiponectin, IL-10, and IL-13 levels, whereas males showed limited improvement. Hepatic triglycerides and F4/80 expression were reduced after Treg expansion, with restored Foxp3 and elevated Il10/Il13 expression, indicating diminished hepatic inflammation.ConclusionEndogenous Treg expansion exerts sex-specific metabolic and anti-inflammatory benefits in db/db T2D mice, with females showing greater improvements in insulin resistance, inflammation, and hepatic lipid metabolism. These findings support Treg-based immunomodulation as a potential therapeutic approach for T2D and emphasize the need for sex-specific considerations in future research.